Performance analysis of a highly available home agent in mobile networks - Abdelgadir , Tageldin; Mohiuddin , Ahmed2; Pathan, Al-Sakib Khan; Mohd Ariff, Abdullah; Shariq, Haseeb (Science Publications, 2011)
Network Mobility as a service is provided by the NEMO protocol in IPv6 environments. NEMO is an extension to MIPv6, and thus inherits the same reliability problems of MIPv6. MIPv6 is not reliable because the Home Agent (HA) is a single point of failure. In order to provide real-time services for MIPv6 networks, reliability should be considered as part of any high availability solution used to deploy Mobile IPv6 networks. Approach: Many approaches have been taken to solve the problem of HA as a single point of failure. In our proposed solution, failure detection and recovery is handled by the home agent. Therefore, recovery is transparent to the mobile network. Results: In this work we opted for using HA redundancy to provide a highly available home agent solution which achieves recovery times suitable for real-time applications.